Use of Linguistic Complexity in Writing Among Chinese EFL Learners in High-Stakes Tests: Insights From a Corpus of TOEFL iBT - Qian, Leyi; Cheng, Yan; Zhao, Yali (Frontiers in Psychology, 2021)
In studies on second language writing, linguistic complexity exhibited by learners has long been regarded as being indicative of writing proficiency. However, there are relatively scant studies focusing on the diversity and structural elaboration of complexity in L2 production data that are extracted from high-stakes tests (like TOEFL and IELTS). By using a large-scale learner corpus collected from TOEFL iBT test, this study is aimed to explore the extent to which the three dimensions of linguistic complexity—syntactic, lexical and morphological complexity, are associated with human scoring in high-stakes tests. In addition, we also tend to tap into within-genre topic effects on learners’ production of complexity measures. To these ends, a total of 1,002 writing samples were collected from TOEFL11 corpus and six automated-coding instruments were used to investigate the variations of complexity among Chinese EFL learners. The results from the correlation analysis, multiple linear regression and independent sample t tests indicated that there was not a linear correlation between the majority of linguistic complexity and human-rated score levels, and proficiency among Chinese EFL learners did not signal a discriminative power in their language production. In the meantime, strong within-proficiency topic effects were found on the majority of measures at the syntactic, lexical and morphological dimensions.